The Analysis on Pre-Service English Teachers’ Teaching Experiences: Perspective on Digital Literacy - Farid Abdul Jabar (Universitas Sultan Ageng Tirtayasa, 2024)
This study aimed to find out the pre-service English teachers’ perception of English Education Department in one of the private universities at Kalimantan Timur toward digital literacy based on their practical teaching experience within the Kampus Mengajar program. The subjects of the research were 4 students of the English Education Department in one of the private universities at Kalimantan Timur who had joined Kampus Mengajar in different schools. This study used a qualitative descriptive case study methodology, and online open response questionnaires and semi-structured interviews were the instruments used for collecting data. This study founds that pre-service teachers have the ability to utilize digital technologies in searching and evaluating relevant learning materials or information when engaging teaching process. The lack of digital technology facilities and poor internet connection were challenges for pre-service English teachers in implementing digital literacy. The result of this study showed that pre-service English teachers have good perception toward digital literacy in the Kampus Mengajar program. This is demonstrated by pre-service English teachers can utilize existing technology to encourage digital literacy during the Kampus Mengajar program.